Philosophy of Education in Fiqh Studies on Ontology, Epistemology, Axiology and Methodology - Nanang Abdillah; Muhammad Najib; Maftuh Maftuh (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Fiqh education in the context of Islam is often understood merely as the transfer of knowledge regarding normative laws. However, the exploration of fiqh education as a process that can shape students' character in accordance with the goals of education, which not only transfers knowledge but also forms individual values and character, has not yet been evident. This is due to the lack of understanding of the essence of fiqh education from the perspective of educational philosophy. This article aims to explain that fiqh should not only be viewed as law but also as education rich in moral and character values. Fiqh education, when analyzed through several philosophical perspectives such as ontological, epistemological, axiological, and methodological studies, reveals its moral and character values. From an ontological perspective, fiqh education can be directed towards understanding the meaning of Islamic education and the relationship between fiqh law and moral values. This shows that fiqh education plays a role in building students' character. In the epistemological aspect, the Qur'an and Hadith serve as the primary sources of knowledge. Teaching methods that include textual, rational, and empirical approaches motivate students to understand the legal context more deeply. Axiology in fiqh education emphasizes the importance of moral values and social responsibility, aiming to shape individuals with high morality. Teaching methodologies are also evolving with new approaches, such as problem-based active learning, to enhance students' interest in understanding the material. Thus, it is hoped that the education of fiqh will not only produce individuals who are well-versed in normative laws but also individuals of noble character in accordance with religious teachings.